ANALISIS PERBANDINGAN KINERJA KEUANGAN BUS DAN UUS ANTARA SEBELUM DAN SELAMA PANDEMI COVID-19 - Asmirawati Asmirawati; Mia Kurniati (Universitas Ahmad Dahlan, 2021)
This study aims to analyze the financial performance of Islamic commercial banks and Islamic business units between before and during the pandemic. This study uses an analysis of the soundness of banks known as CAMEL, which is proxied into the ratio of CAR, NPF, ROA, BOPO and FDR. This study uses a quantitative method by using a comparative approach that compares the similarities or differences of two or more properties and objects studied in a certain frame of mind. This study uses monthly financial reports in 2019-2020. The population of this research is Islamic commercial banks and Islamic business units that issue monthly financial reports. The statistical method used is the descriptive statistical test and Wilcoxon signed-rank test. The results show significant differences in the CAR ratio of Islamic commercial banks, NPF of Islamic commercial banks and Islamic business units, BOPO of Islamic business units, and FDR of Islamic commercial banks. Meanwhile, there was no significant difference between before and during the pandemic for the ROA of Islamic commercial banks and Islamic business units, BOPO of Islamic commercial banks, and FDR of Islamic business units.